Strength and consistency of density dependence in marine fish productivity. Issue 4 (22nd February 2022) - Rindorf, Anna; van Deurs, Mikael; Howell, Daniel; Andonegi, Eider; Berger, Aaron; Bogstad, Bjarte; Cadigan, Noel; Elvarsson, Bjarki Þór; Hintzen, Niels; Savina Roland, Marie; Taylor, Marc; Trijoulet, Vanessa; et al.
Abstract: The correct prediction of the shape and strength of density dependence in productivity is key to predicting future stock development and providing the best possible long‐term fisheries management advice. Here, we identify unbiased estimators of the relationship between somatic growth, recruitment and density, and apply these to 80 stocks in the Northeast Atlantic. The analyses revealed density‐dependent recruitment in 68% of the stocks. Excluding pelagic stocks exhibiting significant trends in spawning stock biomass, the probability of significant density dependence was even higher at 78%. The relationships demonstrated that at the commonly used biomass limit of 0.2 times maximum spawning stock size, only 32% of the stocks attained three quarters of their maximum recruitment. This leaves 68% of the stocks with less than three quarters of their maximum recruitment at this biomass limit. Significantly lower recruitment at high stock size than at intermediate stock size was seen in 38% of the stocks. Density dependence in late growth occurred in 54% of the stocks, whereas early growth was generally density‐independent. Pelagic stocks were less likely to exhibit density dependence in recruitment than demersal and benthic stocks. We recommend that both the degree to which productivity is related to density and the degree to which the relationship changes over time should be investigated. Both of these aspects should be considered in evaluations of whether sustainability and yield can be improved by including density dependence in forecasts of the effects of different management actions.